2022
DOI: 10.3390/nu14234973
|View full text |Cite
|
Sign up to set email alerts
|

Liver Enzymes in a Cohort of Community-Dwelling Older Persons: Focus on Sex Contribution

Abstract: Dysfunctions in liver metabolic activities may increase the risk of cognitive impairment and dementia. In a cohort of community-dwelling older persons investigated for a suspected cognitive decline, we studied the association between liver status and dementia, considering sex and frailty contribution. Serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) concentrations, and the AST/ALT ratio were used to assess liver function in 419 older adults (248 persons with dementia and 171 age- and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 58 publications
2
10
0
Order By: Relevance
“…While an increase in serum AST and ALT levels often holds clinical signi cance as hepatocyte membrane damage can release these enzymes into the bloodstream [34], previous studies have reported that lower AST and ALT levels within their normal ranges and a higher AST-to-ALT ratio were associated with AD diagnosis, poor cognitive performance, and increased Aβ deposition [7][8][9][10][11]. Our results are generally consistent with these earlier ndings.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…While an increase in serum AST and ALT levels often holds clinical signi cance as hepatocyte membrane damage can release these enzymes into the bloodstream [34], previous studies have reported that lower AST and ALT levels within their normal ranges and a higher AST-to-ALT ratio were associated with AD diagnosis, poor cognitive performance, and increased Aβ deposition [7][8][9][10][11]. Our results are generally consistent with these earlier ndings.…”
Section: Discussionsupporting
confidence: 90%
“…Nho et al reported a signi cant association between a higher aspartate aminotransferase (AST) to alanine aminotransferase (ALT) ratio and lower blood ALT levels with AD diagnosis, poor cognitive performance, and increased Aβ deposition [7]. Likewise, other studies have found that lower AST and ALT levels, along with a higher AST to ALT ratio were associated with AD diagnosis and poor cognitive performance [8][9][10][11]. However, despite these intriguing associations, there remains a lack of consensus among studies on the precise relationship between blood AST and ALT levels and AD, as evidenced by Kamada et al, who reported signi cant negative correlations between plasma AST and ALT levels and cognitive decline [12].…”
mentioning
confidence: 99%
“…These findings suggest that reduced ALT levels may contribute to decreased pyruvate levels, leading to disrupted energy balance, compromised glutamate metabolism, and impaired synaptic transmission in the central nervous system. However, it's important to note that Ferri et al (2022) only observed lower serum ALT levels and higher AST/ALT ratios in elderly male dementia patients compared to cognitively normal individuals, with no significant differences observed in elderly females. In contrast, a study by Yokokawa et al (2022) found a significant correlation between serum levels of brain-derived neurotrophic factor (BDNF) and liver enzymes in middle-aged and elderly females, along with a negative correlation between BDNF and liver fibrosis measured by the Fibrosis-4 (FIB-4) index.…”
Section: Liver-derived Factorsmentioning
confidence: 84%
“…For instance, Huynh et al reported that the deletion of ApoE in the hepatocytes of APP/PS1 mice, resulting in decreased plasma ApoE levels but no change in brain ApoE levels, did not in uence the amount of amyloid plaques [65]. Furthermore, there is supporting evidence that serum-based liver function markers, including AST, ALT, and ALP levels and the AST to ALT ratio, are associated with AD diagnosis, poor cognitive performance, and increased Aβ deposition [6][7][8][9][10][11]. Additionally, there is a lack of studies investigating the effects of the APOE ε4 allele on the association of liver function markers with AD pathogenesis and cognition in humans.…”
Section: Discussionmentioning
confidence: 99%